CT-Scan of sediment core PS128_47-1 - Andrea Catalina Gebhardt; Pascal Daub (PANGAEA, 2025)
Core PS128_46-1 was retrieved from a cross-shelf paleo-ice stream trough at the outer shelf in Iceberg Alley (Mac. Robertson Shelf). To aid with lithological investigations, sectional views were extracted from 3D computed tomography (CT) scans performed on a Geotek RXCT scanner. A Thermo Kevex PSX10-65W was used as the x-ray source, run at a voltage of 130 kV with a current of 303 mA. After acquisition with the native Geotek XCT (v.5) software and subsequent pre-processing steps, orthogonal views of each core section were extracted from the central pixel of the reconstructed scan at a resolution of 68 pixels per cm. For better visualization, the histograms of the resulting .tif files were adjusted.